Validation of the method of quantitative phase analysis by X-ray diffraction in API: case of Tibolone. (July 2016) - Silva, R P; Ambrósio, M F S; Epprecht, E K; Avillez, R R; Achete, C A; Kuznetsov, A; Visentin, L C
Abstract: In this study, different structural and microstructural models applied to X-ray analysis of powder diffraction data of polymorphic mixtures of known concentrations of Tibolone were investigated. The X-ray data obtained in different diffraction instruments were analysed via Rietveld method using the same analytical models. The results of quantitative phase analysis show that regardless of the instrument used, the values of the calculated concentrations follow the same systematics with respect to the final errors. The strategy to select a specific analytical model that leads to lower measurement errors is here presented.